Presentific: unveiling the power of presentations for accounting students - Nik Wil, Nor Jaslina; Abdul Hamid, Haslinda; Che Hassan, Anita; Wan Hashim, Wan Murshida (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
This guide aims to assist accounting students in delivering exceptional performance during their class presentations, ensuring they present complex accounting concepts with confidence and clarity. Accounting presentations often challenge students to effectively communicate intricate financial data and principles in a manner that is both academically rigorous and accessible to the audience. Many students struggle with balancing the technical depth of accounting topics while engaging and maintaining the interest of their peers and professors. The lack of a structured approach to creating presentations can result in disorganized, difficult-to-follow presentations, which can undermine a student’s overall performance. The objective of this guide is to provide a comprehensive framework for creating well-structured and compelling accounting presentations. It will focus on key areas such as thorough research, clear explanations, professionalism, and audience engagement. Additionally, the guide will highlight strategies for breaking down complex concepts and presenting them in a way that enhances understanding and retention. By following this guide, students are expected to not only showcase their critical thinking and analytical abilities in accounting but also deliver presentations that captivate and inform their audience. Ultimately, the result will be presentations that are both academically rigorous and engaging, helping students stand out in their class and perform at their best.